2008
DOI: 10.1523/jneurosci.0040-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Fast Subplasma Membrane Ca2+Transients Control Exo-Endocytosis of Synaptic-Like Microvesicles in Astrocytes

Abstract: Astrocytes are the most abundant glial cell type in the brain. Although not apposite for long-range rapid electrical communication, astrocytes share with neurons the capacity of chemical signaling via Ca2+-dependent transmitter exocytosis. Despite this recent finding, little is known about the specific properties of regulated secretion and vesicle recycling in astrocytes. Important differences may exist with the neuronal exocytosis, starting from the fact that stimulus-secretion coupling in astrocytes is volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
190
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(207 citation statements)
references
References 53 publications
16
190
1
Order By: Relevance
“…In astrocytes, the types of vesicles used in Ca 2ϩ -regulated exocytosis are under debate (Bezzi et al, 2004;Li et al, 2008;Marchaland et al, 2008;Parpura and Zorec, 2010). Combining TIRFM with glutamate sniffer recording, we found that astrocytes efficiently released two types of Ca 2ϩ -dependent vesicles, small vesicles and lysosomes, following a single stimulation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In astrocytes, the types of vesicles used in Ca 2ϩ -regulated exocytosis are under debate (Bezzi et al, 2004;Li et al, 2008;Marchaland et al, 2008;Parpura and Zorec, 2010). Combining TIRFM with glutamate sniffer recording, we found that astrocytes efficiently released two types of Ca 2ϩ -dependent vesicles, small vesicles and lysosomes, following a single stimulation.…”
Section: Discussionmentioning
confidence: 90%
“…Using immunoelectron microscopy for vesicle glutamate transporter 1 (VGLUT1), Bezzi et al (2004) identified a type of small vesicle ϳ30 nm in diameter. These have characteristics similar to synaptic vesicles with expression of VGLUT1 and synaptobrevin 2 (Syb2)/vesicleassociated membrane protein 2 (Bezzi et al, 2004;Bowser and Khakh, 2007), and are exocytosed in a Ca 2ϩ -dependent manner (Bowser and Khakh, 2007;Marchaland et al, 2008). Cleavage of Syb2 and cellubrevin/vesicle-associated membrane protein 3 by Clostridium toxins greatly inhibits glutamate release from astrocytes (Bezzi et al, 1998;Araque et al, 2000;Pasti et al, 2001;Jourdain et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The induction of these forms of synaptic plasticity appears to require more extensive synaptic activation than what is required for the induction of the PBD. An interesting possibility is that astrocytes can decode different patterns of synaptic activity into different modes of calcium signaling (Verkhratsky et al, 1998;Perea et al, 2009;Santello and Volterra, 2009) and into release of different constellations of gliotransmitters Bowser and Khakh, 2007;Zhang et al, 2007;Li et al, 2008;Marchaland et al, 2008). The type of calcium signaling as well as the critical gliotransmitters involved in the generation of PBD remains, however, to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies within the last decade have shown that glial cells can release transmitters (which are called gliotransmitters) in a calcium‐ and soluble N ‐ethylmaleimide‐sensitive factor attachment protein receptor (SNARE)‐dependent manner (Marchaland et al, 2008; Martineau, 2013; Montana, Malarkey, Verderio, Matteoli, & Parpura, 2006; Slezak et al, 2012). The physiologic relevance of this process is debated: it may contribute to glial volume regulation (Slezak et al, 2012) and modulate neuronal activity (Araque et al, 2014; Chen et al, 2012; Perez‐Alvarez, Navarrete, Covelo, Martin, & Araque, 2014; Takata et al, 2011).…”
Section: Introductionmentioning
confidence: 99%